A novel approach for treating acid mine drainage by forming schwertmannite driven by a combination of biooxidation and electroreduction before lime neutralization. (1st August 2022) - Song, Yongwei; Guo, Zehao; Wang, Rui; Yang, Linlin; Cao, Yanxiao; Wang, Heru
Highlights: Biooxidation–electroreduction cyclic mineralization was proposed to treat AMD. AMD treat efficiency was improved compared with chemical or biological method. Fe and SO4 2− in AMD were recovered as schwertmannite after cyclic mineralization. Cyclic mineralization can reduce the amount of AMD neutralized sludge by 6 times. Abstract: Acid mine drainage (AMD) contains abundant iron, sulfates, and various metal ions, and it causes environmental pollution. The traditional AMD lime neutralization forms a layer of iron hydroxide and gypsum on the surface of the lime particles, preventing continuous reaction and leading to excessive lime addition and neutralized sludge production. In this study, an approach for treating AMD using a cyclic process of biooxidation and electroreduction before lime neutralization was proposed, in which the Fe 2+ in AMD was oxidized to Fe 3+ and induced to form schwertmannite through Acidithiobacillus ferrooxidans . The remaining Fe 3+ was reduced to Fe 2+ using an electric field. After three biooxidation and two electroreduction cycles, 98.2% of Fe and 62.4% of SO4 2− in AMD precipitated as schwertmannite (Fe8 O8 (OH)5.16 (SO4 )1.37 ). The yield of schwertmannite reached 33.98 g/LAMD, with a high specific surface area of 112.59 m 2 /g. The lime dosage and sludge yield of the treated AMD in the subsequent neutralization stage (pH = 7.00) decreased by 85.0% and 74.5%, respectively, than those of raw AMD. The pilot test results showed that the integrated treatment of biooxidation–electroreduction cyclic mineralization and lime neutralization has practical applications. Graphical abstract: Image, graphical abstract